UMUMIY O‘RTA TA’LIM TIZIMIDA SUMMATIV BAHOLAShNING NAZARIY ASOSLARI - Erkabayev, X.S. (SCIENCE and SOCIETY, 2025)
The article provides an in-depth analysis of the theoretical and methodological foundations of summative assessment used in the general secondary education system. It highlights the role of assessment in the pedagogical process, its main principles, functions, and its significance in the development of students' knowledge, skills, and competencies. Additionally, the article thoroughly examines the impact of assessment results on the quality of education and their influence on the interaction between teachers and students.
Keywords: summative production; teaching aids; quality of education; implementation results; measurement criteria; international experience; written and oral surveys; scoring system; rating; systematicity; methodology